Penggunaan Metode Jaritmatika Dalam Meningkatkan Motivasi Belajar - Muhamad Khoirul Umam (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Mathematical subjects are indicated as subjects that are difficult and saturating and are also less attractive to many students. Teachers as educators are required to be able to have skills in making interesting classroom activities. Activities that can make students interested can be in the form of games. So the researcher raises the question in the form of how games containing elements of mathematics can stimulate students to learn multiplication operations and also how the use of the method of Jarimatika on multiplication of mathematics subjects can increase learning motivation of IV students of MI Miftakhul Ulum Slorok, Garum, Blitar. To answer the research formula, researchers used a qualitative research approach with the type of classroom action research in the form of a spiral cycle with activities including planning, action, observation, and reflection. Data collection techniques used are: (1) observation; (2) questionnaire; and (3) interviews; (4) documentation. Data obtained from actions are then analyzed. Qualitative data are analyzed qualitatively, while the data are quantitative, enough to use descriptive analysis and visual presentation. So the results of the research using the method of Jarimatika on multiplication of mathematics subjects in fourth grade students of MI Miftakhul Ulum sub-district, Garum, Blitar regency can improve student learning outcomes from the pre test results of only 43.75% to 81.25% in cycles I and 93, 75% in cycle II. Indicators of increasing student motivation can be seen from the increased enthusiasm and enthusiasm of students in participating in teaching and learning activities, there does not appear to be a feeling of laziness and fatigue, they always show joy and happiness during the lessons, and the curiosity they apply by always practicing and memorizing the use of the jarimatika method when they calculate multiplication.